Pengembangan LKPD untuk Meningkatkan Hasil Belajar Peserta Didik Sosiologi Kelas XI IPS SMAN 1 Payung Sekaki Kabupaten Solok - Septivana Tia Ananda; Ike Sylvia (Naradidik: Journal of Education and Pedagogy, 2022)
Sociology learning with limited teaching material makes it difficult for students to find material, in addition unsatisfactory learning outcomes. Therefore it is necessary to design teaching materials that are able to improve students’ learning outcomes and achieve mastery of the material. One of the teching materials that can support the subject of sociology is the discovery inquiry based LKPD teaching material. This research on the development of LKPD is a type of RND research with the ADDIE development model consisting of: (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. This research is based on construcrivism theory, namely building a modern culture life structure through the involvement of students to be active in the construction of meaning and knowledge. Based in the application of LKPD, student obtained a pretest with an average of 35,4 and an average posttest of 68,6, that of students’ critical thingking before and after learning. Then the normality test, homogeneity test and t test were carried out.